The Potency of Typical Plants of Central Sulawesi Province to Prevent Iron Deficiency Anemia: Experimental Study - Mulia Sakti, Putri; Hi. Amir Sene, Ikhsan; Ramadhan, Kadar (YCAB Publisher, 2024)
Background: Central Sulawesi falls within the Wallacea region, making it home to various endemic flora and fauna. One distinctive plant in Central Sulawesi is the Moringa tree. The Moringa tree, especially its leaves, was often used as a culinary ingredient known as sayurkelor in the traditional cuisine of the Kaili ethnic group in Central Sulawesi Province. Objective: This research aimed to determine the effectiveness of moringa leaf extract in increasing hemoglobin levels and erythrocyte count. Method: Twenty-four male Wistar rats strain (Rattusnorvegicus) 9−10 weeks old and 200−250 grams were divided into four groups (n=6), normal as a no treatment, negative control, ethanol extract, and positive control during the 15thday. Blood samples on the 15thday were administered to determine blood count. Result: The resultsof this study showed differences in hemoglobin and erythrocyte levels in the four experimental groups.The significant difference in average hemoglobin levels between Group 2 and Group 3 with a P-value <0.05 (P value 0.00). The difference between Group 2 and Group 4 is significant with a P-value <0.05 (P value 0.00), and the difference between Group 3 and Group 4 is significant with a P-value <0.05 (P value 0.03). the significant difference in the average erythrocyte counts between Group 2 and Group 3 with a P-value <0.05 (P value 0.00). The difference between Group 2 and Group 4 is not significant with a P-value >0.05 (P value 0.07). The difference between Group 3 and Group 4 has a P-value >0.05 (P value 0.63). Conclusion: The research results indicate that pregnant Wistar rats experienced hemodilution characterized by a decrease in hemoglobin and erythrocyte levels during pregnancy. However, after being given ethanol extract from moringa leaves, there was an increase in hemoglobin and erythrocyte levels. Keywords: Extract; ethanol; moringa; oleifera; hemoglobin